PEMBERIAN MAKANAN TAMBAHAN UNTUK MENGATASI GIZI KURANG PADA BALITA KURUS - Dari, Wulan; Puspitasari, Maya; Susilawati, Susilawati; Mawarsih, Dwi Inti; Yuliani, Nur; Lizah, Relita; Sulistiana, Indri; Sofiyah, Siti Khofsoh; Sukartini, Sukartini; Santika, Agus Zella (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
Toddlers are a group vulnerable to health problems, especially malnutrition, considering the rapid growth and development phase at this time. Malnutrition in toddlers can have a severe impact on the child's brain development and intelligence and can even result in death. An observational study in Dono Mulyo Village, Way Kanan Regency, Lampung, in May 2024 found three cases of underweight toddlers out of 95 toddlers observed. Handling this problem, including providing additional food, is essential. Community practice activities aim to overcome the problem of underweight toddlers by giving extra food, educating mothers about the importance of balanced nutrition for toddlers, and increasing mothers' knowledge about balanced nutrition for toddlers. The method used is counselling to mothers of toddlers. Activities are carried out in several stages: preparation, implementation of activities, evaluation, and preparation of reports. Knowledge assessment is carried out by giving a pretest before counselling and a posttest after counselling. Apart from that, toddler feeding patterns are measured as a result of changes in attitudes, which is done with the Child Feeding Questionnaire (CFQ). The results of community practice activities show that outreach activities can increase mothers' knowledge about the importance of balanced nutrition for toddlers and demonstrate accuracy in toddler feeding patterns.